Agricultural production amid conflict: the effects of shocks, uncertainty, and governance of non-state armed actors (2014)
This paper examines the effect of conflict on agricultural production of small farmers. First, an inter-temporal model of agricultural production is developed, in which the impact of conflict is transmitted through two channels: violent shocks and uncertainty brought about by conflict. The model shows how conflict induces sub-optimal agricultural decisions in terms of land use and investment. We test the model using a unique household survey applied to 4,800 households in four micro-regions of Colombia. The survey collects detailed information on household economic conditions, incidence of violent shocks, and the presence of non-state armed actors. The results show that conflict affects agricultural production through different channels. In regions with intense conflict, households reduce the amount of land allocated to perennial crops, increase production of seasonal crops, and cut back investments. Households seem to learn to live amid conflict. Recent presence of non-state armed actors induces farmers strongly to cut back land use for perennial crops, pasture, and investments. As presence is more prolonged, farmers increase land use for pasture and investments rebound. However, total agricultural production may be lower because shocks and presence result in more land being idle. Households habituate to conflict, yet at a lower equilibrium.